THE CHENGE OF PARADIGM OF PRIMARY CLASSES TEACHERS TREINING IN CONDITIONS OF INFORMATION SOCIETY DEVELOPMENT - Kushnir, Н.О.; Vinnyk, Т.О. (Journal of Information Technologies in Education (ITE), 2016)
The emergence and wide dissemination of new digital technologies in all spheres of life significantly changes the structure of the labor market (there are new profession change dramatically professional activities) and the requirements of employers (the ability to learn independently throughout the life, to evaluate critically information, team work becomes more important, Maturity than a specific set of knowledge and skills). At the same time, today's children live in crowded information space, which highlights the issue of formation of information culture of their bases from an early age and quality of development needed for successful self-realization in the information society. This leads to changes in the entire education system, in particular the training of future elementary school teachers. A retrospective analysis of the use of information and communication technologies in education confirms the occurrence of such technologies for the development of children. Analysis of practice of training of future elementary school teachers shows the insufficient level of awareness of modern ICT capabilities, which are mainly used to support the traditional educational process, not the implementation of new learning approaches. The article analyzes the impact of the development of modern information and communication technologies for education in the context of professional training of future elementary school teachers.